On intimate care in men: A review - Zofia A. Niewozinska; Luiza R. Sakaniya; Irina M. Korsunskaya (ZAO "Consilium Medicum", 2024)
Even though intimate hygiene plays an essential role in the prevention of various genital diseases, there are currently few studies on this topic. There is a wide range of diseases that affect the male genital organs. There is a wide range of diseases that affect the male genital organs. Inflammation of the glans penis (balanitis) occurs in 3-11% of males during their lifetime; one of its leading causes is poor hygiene. However, many non-venereal dermatoses occur in this anatomical region. Most often, patients complain of itching, as well as pain, burning, and various rashes. The most common reason for seeking medical attention is irritant contact dermatitis. Various allergens cause more acute reactions in the anogenital region due to the structural features of the skin of the genitals. Components of detergents and hygiene products, accessories for sexual practices, medications, and contraceptives can become provoking factors of genital allergic dermatitis. Among the dermatoses affecting the male genitalia, lichen planus should be noted, which occurs in males twice as often as in females, and the oral mucosa is often involved in the inflammatory process. Lichen sclerosus can also occur on the skin of the penis, leading to phimosis, a decrease in quality of sexual life, and often requiring circumcision. Psoriasis also can affect the anogenital area. Rashes may be isolated, but other anatomical areas are also involved in most cases. Psoriatic lesions of the genitals are visually different from typical elements in other areas of the skin. Minimizing discomfort due to these diseases is possible by using specialized care products. The skin of the genitals in men has specific features that are important to consider when developing the composition of the products.